Clinical development of the GnRH agonist leuprolide acetate depot - Kristof Chwalisz, M.D., Ph.D (Elsevier, 2023)
Leuprolide acetate is the first GnRH agonist that entered clinical development after the discovery of the native GnRH. Several long-acting depot formulations of leuprolide acetate (ranging from 1-month to 6-month intramuscular injections) have been successively developed for various suppressive treatments in men, women, and children, which are available in the United States and globally. This mini review aims to summarize the key clinical studies that led to regulatory approval of leuprolide acetate depot suspension for injection.